2018
DOI: 10.1002/jia2.25128
|View full text |Cite
|
Sign up to set email alerts
|

The impact of population dynamics on the population HIV care cascade: results from the ANRS 12249 Treatment as Prevention trial in rural KwaZulu‐Natal (South Africa)

Abstract: IntroductionThe universal test and treat strategy (UTT) was developed to maximize the proportion of all HIV‐positive individuals on antiretroviral treatment (ART) and virally suppressed, assuming that it will lead to a reduction in HIV incidence at the population level. The evolution over time of the cross‐sectional HIV care cascade is determined by individual longitudinal trajectories through the HIV care continuum and underlying population dynamics. The purpose of this paper is to quantify the contribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 23 publications
(32 reference statements)
2
41
0
1
Order By: Relevance
“…Among all HIV-positive individuals, regardless of knowledge of their HIV-positive status, ART coverage was approximately 85% in women and approximately 75% in men in both the Zambian and SA communities, around 10% higher than after the first 2 years of the intervention and up from around 45% at the start of the study. Progress toward reaching high testing and treatment coverage was slowed by high rates of mobility and in-migration among both men and women, with mobile individuals and inmigrants having lower knowledge of HIV-positive status and ART coverage than "stable" residents, as reported previously [7] and also found in the ANRS 12249 TasP trial [18]. The way in which the PopART intervention was delivered through "rounds" of visits to every household meant that it was effective in identifying and including newly resident individuals, but only with a delay.…”
Section: Discussionmentioning
confidence: 61%
“…Among all HIV-positive individuals, regardless of knowledge of their HIV-positive status, ART coverage was approximately 85% in women and approximately 75% in men in both the Zambian and SA communities, around 10% higher than after the first 2 years of the intervention and up from around 45% at the start of the study. Progress toward reaching high testing and treatment coverage was slowed by high rates of mobility and in-migration among both men and women, with mobile individuals and inmigrants having lower knowledge of HIV-positive status and ART coverage than "stable" residents, as reported previously [7] and also found in the ANRS 12249 TasP trial [18]. The way in which the PopART intervention was delivered through "rounds" of visits to every household meant that it was effective in identifying and including newly resident individuals, but only with a delay.…”
Section: Discussionmentioning
confidence: 61%
“…provision of services that are tailored to the needs of a given individual or sub‐population to improve outcomes and efficiencies within health systems). While modelling data suggest an AIDS‐free generation may be possible and community‐based “fast‐track” ART initiation can achieve high rates of virological suppression , recent data on reducing HIV incidence has been disappointing . More data are needed to understand the mechanisms behind these findings and the role adherence plays, particularly among vulnerable populations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, ART initiation remained similar between arms: all ART initiations within trial clinics represent 17% (662/3940) of the PLHIV population in the intervention arm, compared with 12% (554/4623) in the control arm. In addition, the PLHIV population turnover in the trial area was high, more than one fifth being replaced every year, mainly due to out-and in-migration as well as the continuous inflow of new HIV infections, attenuating the impact of the interventions on the cascade of HIV care and subsequently the differences between arms [26]. Tanser et al, using data from another rural community in KwaZulu-Natal, found that HIV incidence was not directly associated with PVS but rather with population viral load metrics that account for HIV prevalence [27].…”
Section: Discussionmentioning
confidence: 99%